C1, α-regularity for steady flows of electrorheological fluids in 2D. (April 2023) - Sin, Cholmin
Abstract: We prove interior C 1, α -regularity of every weak solution and the existence of global C 1, α -solutions for steady flows of electrorheological fluids with Dirichlet type boundary condition under 3 2 < p ( x ) < ∞ in 2D.